Enablers and Barriers to Youth Employment: An Employment Ecosystem Approach - Panos Karanikolas; Joanne Xiaolei Qian-Khoo (Encyclopedia, 2025)
An “employment ecosystem” approach acknowledges that factors affecting employment are never the result of one singular factor but are the product of multiple, intersecting, and mutually reinforcing factors at the individual level (personal attributes and immediate circumstances), relationships and wider community, the workplace, and the wider macro-level (societal and structural factors, such as legislation, government policies, and macro-economic trends). Originally conceptualised within the context of employment for people with disabilities, the employment ecosystem approach provides an ecological perspective that can be used to understand the ingredients of inclusive employment more generally. This entry applies an employment ecosystem analytical lens to explore and identify enablers and barriers to youth employment in the Australian context, based on reviews of published research and reports of initiatives and programs targeting youth employment. Findings include the need to recognise the centrality of support from broader community resources, including family and community-based support, employers and co-workers, policy, and legislation. It provides evidence-based insights for practitioners and researchers interested in the development and implementation of inclusive employment practices.